2010
DOI: 10.1002/adma.200903469
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated‐Polymer‐Functionalized Graphene Oxide: Synthesis and Nonvolatile Rewritable Memory Effect

Abstract: An ITO/TPAPAM‐GO/Al memory device (see figure; ITO = indium tin oxide, TPAPAM‐GO = graphene oxide covalently grafted with triphenylamine‐based polyazomethine) exhibits typical bistable electrical switching and a nonvolatile rewritable memory effect with a turn‐on voltage of −1.0 V and an ON/OFF‐state current ratio of more than 103. Both ON and OFF state are stable under a constant voltage stress and survive up to 108 read cycles at a read voltage of −1.0 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
234
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 406 publications
(242 citation statements)
references
References 30 publications
4
234
0
2
Order By: Relevance
“…One of the approaches for improving the solubility of the graphene material is to modify GO by using a chemical method. [59][60][61] For example, Zhuang et al 62 demonstrated a single-layer hybrid bistable memory containing GO sheets covalently grafted with soluble conjugated polymer triphenylamine-based polyazomethine (TPAPAM). The device was fabricated by using a simple spincoating technique, and the TPAPAM-GO-based memory device exhibited typical bistable electrical switching and a nonvolatile rewritable memory effect, with a turn-on voltage of about À1 V and an ON/OFF current ratio of about 10 3 .…”
Section: Electrical Memory Devicesmentioning
confidence: 99%
“…One of the approaches for improving the solubility of the graphene material is to modify GO by using a chemical method. [59][60][61] For example, Zhuang et al 62 demonstrated a single-layer hybrid bistable memory containing GO sheets covalently grafted with soluble conjugated polymer triphenylamine-based polyazomethine (TPAPAM). The device was fabricated by using a simple spincoating technique, and the TPAPAM-GO-based memory device exhibited typical bistable electrical switching and a nonvolatile rewritable memory effect, with a turn-on voltage of about À1 V and an ON/OFF current ratio of about 10 3 .…”
Section: Electrical Memory Devicesmentioning
confidence: 99%
“…This type of modification has a special interest in the dispersion of functionalized GO in different solvents (polar or non-polar), this is due to the fact that the family of silanes provide a wide range of terminal functional groups. The functionalization of GO via carboxylic acids is one of the most common approaches and is possible by prior activation of these groups through various agents such as thionyl chloride (SOCl 2 ) (Niyogi, Bekyarova et al 2006;Liu, Xu et al 2009;Zhang, Huang et al 2009;Karousis, Economopoulos et al 2010;Zhuang, Chen et al 2010), 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC) (Liu, Robinson et al 2008), N, N'-dicyclohexylcarbodiimide (DCC) (Veca, Lu et al 2009) and 2-(7-aza-1H-benzotriazole-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (Hatu) (Mohanty and Berry 2008). Subsequent addition of nucleophilic species, such as amines and hydroxyl, allow the formation of covalent bonds with functional groups of the graphene oxide through formation of amide or ester groups.…”
Section: Covalent Functionalizationmentioning
confidence: 99%
“…7 In our previous work, we designed a series of D-A-type functional polymers. [8][9][10][11][12][13][14][15][16][17][18][19] The device based on conjugated poly[9,9-bis(4-diphenylaminophenyl)-2,7-fluorene] donors covalently bridged with Disperse Red 1 acceptors (DR1-PDPAF-DR1) exhibited an accessible rewritable memory characteristic. 10,17 The excitation of donor promoted CT to the conjugated channel, finally the electrons were at LUMO1 or further at LUMO2 and gave rise to a conductive charge separation state.…”
Section: Introductionmentioning
confidence: 99%
“…14 TPA-based conjugated polyazomethine covalently grafted with graphene oxide (TPAPAM-GO) was directly used to fabricate nonvolatile rewritable memory devices. 11 Electrons transmitted from the HOMO of the hole-transporting polymer TPAPAM into LUMO of graphene layer by intramolecular CT interaction established charge transport pathways and switched the device from the OFF to ON state. The effective electron delocalization in graphene nanosheets might stabilize the CT state of TPAPAM-GO, leading to a nonvolatile nature.…”
Section: Introductionmentioning
confidence: 99%